2003
DOI: 10.1046/j.1462-2920.2003.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

The marine firewormHermodice carunculatais a winter reservoir and spring‐summer vector for the coral‐bleaching pathogenVibrio shiloi

Abstract: Vibrio shiloi, the causative agent of bleaching of the coral Oculina patagonica in the Mediterranean Sea, is present in all bleached O. patagonica corals in the summer (25-30 degrees C), but can be not detected in the coral during the winter (16-20 degrees C). Furthermore, the pathogen can not survive in O. patagonica at temperatures below 20 degrees C. Using fluorescence in situ hybridization (FISH) with a V. shiloi-specific oligonucleotide probe, we found that the marine fireworm Hermodice caranculata is a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(127 citation statements)
references
References 18 publications
4
122
0
1
Order By: Relevance
“…Vectors are living agents that transmit pathogens (Stedman 2000) and in the coral reef environment may include predatory and/or herbivorous arthropods, annelids, mollusks, echinoderms, and fishes. The only known vector for a coral disease is the marine fireworm Hermodice carunculata, which transmits Vibrio shiloi, the causal agent of VSB, to its coral host (Sussman et al 2003). Contaminated water is an inanimate mode of indirect disease transmission and waterborne pathogens are significant in marine ecosystems.…”
Section: Disease Terminologymentioning
confidence: 99%
See 1 more Smart Citation
“…Vectors are living agents that transmit pathogens (Stedman 2000) and in the coral reef environment may include predatory and/or herbivorous arthropods, annelids, mollusks, echinoderms, and fishes. The only known vector for a coral disease is the marine fireworm Hermodice carunculata, which transmits Vibrio shiloi, the causal agent of VSB, to its coral host (Sussman et al 2003). Contaminated water is an inanimate mode of indirect disease transmission and waterborne pathogens are significant in marine ecosystems.…”
Section: Disease Terminologymentioning
confidence: 99%
“…During winter, V. shiloi is present in the VBNC state inside H. carunculata, and during summer, when the worm feeds on O. patagonica, the VSB pathogen is transmitted to a few coral colonies. This indirect transmission serves to restart the infection process, and the infectious VSB then spreads from colony to colony (Sussman et al 2003).…”
Section: Vibrio Shiloi -Induced Bleachingmentioning
confidence: 99%
“…Most diseases are caused by pathogens such as bacteria, cyanobacteria and fungi. Pathogens can be delivered to coral reefs via terrestrial runoff (Sutherland et al 2004), or transmitted by biological vectors (Sussman et al 2003). Recent studies have highlighted the role of elevated levels of dissolved organic carbon, a common component of sewage and organic discharge, to tissue sloughing (symptomatic of many diseases) and increased coral mortality (Table 2; Kuntz et al 2005;Kline et al 2006).…”
Section: Coral Diseasesmentioning
confidence: 99%
“…Observations and field data collected over the years indicate an increase in breakage of reef-building coral branches, decline in coral species diversity and recruitment rates and overall number of live coral colonies in Eilat's nature reserve (Zakai and Chadwick-Furman 2002). There is an increased incidence of diseased coral (Sussman et al 2003) and fish, shown to be linked with anthropogenic activity (Diamant et al 2000;Diamant 2001;Colorni et al 2002).…”
Section: The Red Seamentioning
confidence: 99%